Luke - Spencer, F. Scott (Franklin Scott) (W.B. Eerdmans Pub. Co.; Grand Rapids, Mich., 2019)
"This volume is a commentary on Luke in the Two Horizons New Testament Commentary series. The author uses an approach that bridges the gap between biblical studies and systematic theology, offering section-by-section exegesis of the New Testament texts in close conversation with theological concerns"--
Introduction : reading Luke theologically : a pilgrim's prospectus -- "Minifesto" for theological interpretation -- Interpretation : theological commentary on Luke knowing God the Savior with solid assurance through the story of Jesus (1:1-4) -- Knowing God the Creating Savior in the birth and growth of Jesus (1:5-4:13) -- Birth announcements and celebrations (1:5-80) -- Jesus's birth and childhood (2:1-52) -- Jesus-s baptism and temptation (3:1-4:13) -- Knowing God the Liberating Savior in the teachings and miracles of Jesus (4:14-9:50) -- Proclaiming the freedom of jubilee (4:14-6:16) -- Leveling the field of opportunity (6:17-8:3) -- Cultivating the fruit of salvation (8:4-9:50) -- Knowing God the Seeking Savior in the travels and parables of Jesus (9:51-19:44) -- Stage 1 : Refusing to retaliate and destroy in the face of rejection and prejudice (9:51-13:21) -- Stage 2 : Longing to gather and protect in the face of opposition and obstinacy (13:22-17:10) -- Stage 3 : Choosing to restore and welcome in the face of ingratitude and otherness (17:11-18:30) -- Stage 4 : Pressing on to suffer and save in the face of injustice and ignorance (18:31-19:44) -- Knowing God the Suffering Savior in the death and resurrection of Jesus (Luke 19:45-24:53) -- Challenging the Temple establishment (19:46-21:38) -- Incarnating the World-'s suffering (22:1-24:53) -- Integration : theological reflection on Luke reflecting on Luke systematically -- Theological knowing -- Anti-Gnostic knowing -- Progressive knowing -- Trinitarian theology -- Spiritual theology -- Creational theology -- Social theology -- Passional theology.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries